The synthesis and Co(II), Ni(II), Cu(II) and UO2(VI) complexes of 1,2-O-benzal-4-aza-7-aminoheptane - Sekerci, M; Alkan, C (Taylor & Francis Inc, 1999)
1,2-O-Benzal-4-aza-7-aminoheptane (L) has been synthesized starting from 1-chloro-2,3-O-benzalpropane, which has been prepared from the reaction of epichlorohydrin and benzaldehyde. The complexes of this ligand with Co(II), Ni(II), Cu(II) and UO2(VI) salts were prepared. The structures of the ligand and its complexes are proposed based on elemental analyses, IR, UV-VIS, H-1 and C-13 NMR spectra, magnetic susceptibility measurements, thermogravimetric analyses (TGA) and differential thermal analyses (DTA).
Keywords: Dioxouranium(Vi) Complexes; Nickel(Ii); Palladium(Ii); Platinum(Ii); Copper(Ii); Cobalt(Ii); Polymers; Oximes; Acid